PHASE RELATIONS OF POTASSIUM-BEARING CLINOPYROXENE IN THE SYSTEM CAMGSI2O6-KALSI2O6 AT 7 GPA - Safonov O.G.; Litvin Y.A.; Perchuk L.L.; Bindi L.; Menchetti S. (My University, 2003)
The pseudo-binary system CaMgSi2O6-KAlSi2O6, modeling the potassium-bearing clinopyroxene (KCpx) solid solution, has been studied at 7GPa and 1,100–1,650C. The KCpx is a liquidus phase of the system up to 60mol% of KAlSi2O6. At higher content of KAlSi2O6 in the system, grossular-rich garnet becomes a liquidus phase. Above 75mol% of KAlSi2O6 in the system, KCpx is unstable at the solidus as well, and garnet coexists with kalsilite, Si-wadeite and kyanite. No coexistence of KCpx with kyanite was observed. Above the solidus, KAlSi2O6 content of the KCpx coexisting with melt increases with decreasing temperature. Near the solidus of the system (about 1,250C) KCpx contains up to 5.6wt% of K2O, i.e. about 22–26mol% of KAlSi2O6. Such high concentration of potassium in KCpx is presumably the maximal content of KAlSi2O6 in the Fe-free clinopyroxene at 7GPa. In addition to the major substitution MgM1C2Al1K2, the KCpx solid solution contains Ca-Eskola and only minor Ca-Tschermack components. Our experimental results indicate that the natural assemblage KCpx+grossular-rich garnet might be a product of crystallization of the ultra-potassic SiO2-rich alumino-silicate mantle melts (>200km).